2022
DOI: 10.1039/d2ee00548d
|View full text |Cite
|
Sign up to set email alerts
|

Structure-controlled graphene electrocatalysts for high-performance H2O2 production

Abstract: Metal-free carbon materials have emerged as cost-effective and high-performance catalysts for the production of hydrogen peroxide (H2O2) through the two-electron oxygen reduction reaction (ORR). Here, we show that 3D crumpled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…A slight shift of (002) peak position can be dependent on different amounts of functional groups within each NCG sample. [ 32,47 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A slight shift of (002) peak position can be dependent on different amounts of functional groups within each NCG sample. [ 32,47 ]…”
Section: Resultsmentioning
confidence: 99%
“…These low O/C ratios of NCGs indicate that the aerosol process at the high temperature of 1000 °C effectively reduced NCGs. [ 47 ] The S2p peak was additionally observed in the survey scan of NCG‐CYS sample due to the sulfhydryl group of l‐cysteine, and its atomic sulfur to carbon ratio was determined to be 0.01. All samples showed a CN peak with an atomic N to carbon (N/C) ratio of 0.03, indicating similar amounts of N‐doping to graphene.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in previous experimental and theoretical research, the catalytic performance of oxygen species functionalized carbon materials (O−C) is not only positively correlated with active oxygen species but also the crystallinity (i. e., the degree of graphitization) of carbon substrate [14,18,19] . For instance, the highly‐graphitized carbon nanotubes with the active oxygen species (O−C=O and C−O−C) showing ∼90 % H 2 O 2 selectivity [15,20,21] . Nevertheless, a massive consumption of strong oxidizer and washing water during the oxidation of (e. g., graphite, carbon nanotubes) brings severe environmental problems.…”
Section: Introductionmentioning
confidence: 86%
“…201,237 Researches have demonstrated that they can achieve the simultaneous dehalogenation and oxidation of halide. 237 Because oxygen can be cathodically reduced into H 2 O 2 on carbonaceous catalysts, [238][239][240] the integration of electro-Fenton and membrane separation has drawn increasing attention to remove various organic pollutants (Fig. 6a), such as dye molecules, 241,242 persistent oxalate, 170,171 and antibiotics.…”
Section: Organic Pollutant Removalmentioning
confidence: 99%